A Latent Class Analysis of DUI Offender Motivation and Awareness as Predictors of Performance While on Alcohol Ignition Interlocks. (4th May 2021) - Scherer, Michael; Beck, Kenneth; Taylor, Eileen P.; Romosz, Ann; Voas, Robert; Romano, Eduardo
ABSTRACT: Introduction: . Alcohol ignition interlock devices (IID) reduce rates of drinking and driving. The interlock offers an opportune time for tailoring targeted interventions to develop habits to separate drinking from driving among this high-risk population. This study identified different types of IID users upon whom targeted interventions could be developed. Methods: Participants (N = 114) were assessed at IID installation and again six months later. Latent class analysis (LCA) was conducted using drinking environment, drinking motivation, social support, drug use, and problem drinking behaviors as indicators. Multivariate regression analyses were conducted comparing latent class assignment with impaired driving attempts. Results: LCA supported a 4-class model where 14.8% of participants fell into the low use/high awareness class; 30.6% fell into the heavy use/high awareness class; 30.6% fell into the mixed use/high awareness class; and 24.0% fell into the moderate use/low awareness class. Drivers in the moderate use/low awareness condition had increased early morning BAC lockouts. Conclusions: These typologies demonstrate important differences within high risk drivers. Indeed, drivers who fell into the moderate use/low awareness class may not have considered their alcohol-related behaviors problematic. This information could lend itself to the development of targeted interventions to address subgroups of drinking drivers.